Pengaruh Pengetahuan dan Karakteristik Bank Terhadap Minat Menabung Mahasiswa di Bank Syariah Dengan Religiusitas Sebagai Variabel Moderasi - Rokhani, Sri; Nurkhin, Ahmad (Universitas Negeri Semarang, 2021)
The purpose of this study is to examines the knowledge and characteristics of banks variables toward the student’s saving intention in Islamic banks with religiosity as moderation variable. The object of the study is the Economic Education Department students year 2015 of Semarang State University who took Islamic Economics courses. The sampling technique uses probability sampling with the proportionate random sampling method. The sample involved 200 students, calculated by using the Slovin formula of a population of 380 students. The data collection techniques used questionnaires, meanwhile the data analysis technique used descriptive statistical analysis, and moderated regression analysis (MRA). The results of the study show that knowledge has a positive and significant influence on students' savings intention in Islamic Banks. Bank characteristics has a positive and significant influence on student savings intention in Islamic Banks. Religiosity is significantly able to moderate the influence of knowledge on students' savings intentions in Islamic Banks. Religiosity significantly can moderate the influence of bank characteristics on students' savings intentions in Islamic Banks. This study concludes that knowledge and characteristics of bank are proven influencing the students saving intention in islamic bank, and religiosity is proven to be a moderating variable.